The Effect of Snakehead Fish (Channa Striata) Extract On Superoxide Dismutase (SOD) Levels And Pancreatic Histology Phytology In A Rat Model With Liver Cirrhosis - OK Yulizal; Andre Priyatama; Yuliani Mardiati Lubis (CV. Inara, 2025)
Liver cirrhosis results in progressive liver tissue damage and systemic oxidative stress affecting the pancreas. This study aimed to evaluate the effects of snakehead fish (Channa striata) extract on superoxide dismutase (SOD) levels and pancreatic histopathology in a rat model of liver cirrhosis.Method:An experimental study used male Wistar rats induced with CCl₄. The rats were divided into groups treated with snakehead fish extract at different doses (100, 150, 200 mg/kgBW) orally for two weeks. The parameters measured included body weight, pancreatic SOD activity, and histopathological analysis using Hematoxylin-Eosin staining. Data analysis used One Way ANOVA and post-hoc test with a significance level of p < 0.05.Results:Snakehead fish extract significantly increased pancreatic SOD activity in a dose-dependent manner and improved pancreatic histology compared to the control cirrhosis group. Body weight and organ function increased, indicating reduced oxidative damage and tissue regeneration.Conclusion:Snakehead fish extract shows potential as a natural antioxidant therapy in reducing oxidative stress and repairing pancreatic tissue in cirrhosis models. Further research is needed to isolate the active compounds and verify their clinical effectiveness.